Two new species and one new record species of genus Arrenurus Dugès, 1834 (Acari, Hydrachnidia, Arrenuridae) from China - Zheng, Yulin; Gu, Xinyao; Guo, Jianjun; Zhang, Runzhi (Zootaxa, 2021)
Three species of the genus Arrenurus Dugès, 1834 are described in detail from China, of which Arrenurus (Arrenurus) ancoralis Zheng & Guo sp. nov. and Arrenurus (Arrenurus) unguiculus Zheng & Guo sp. nov. are new to science, and Arrenurus (Truncaturus) isikliensis Boyaci & Özkan, 2004 is recorded for the first time for the Chinese fauna. Arrenurus (A.) ancoralis can be distinguished by D3 on big humps and each with a small protrusion bearing D3 gland; the petiole is well-developed, the middle part contracted, slightly enlarged posteriorly; the ligulate process extending beyond the posterior margin of the petiole and triangle-shaped. Arrenurus (A.) unguiculus can be distinguished by the ligulate process extending beyond the posterior margin for half of petiole length, and nail-shaped. Arrenurus (A.) isikliensis is recorded for the Chinese fauna for the first time. Detailed descriptions and illustrations of the new and the newly recorded species are given in this paper.